Understanding cash waqf: it's role towards alleviating poverty in contemporary context - Ali, Md. Yousuf; Khanom, Fahima (Universiti Sains Islam Malaysia, 2014)
Cash Waqf is one of the potential and effective means in contemporary society in alleviating poverty. From the Islamic SharÊah perspective, the establishment of the institution of waqf is permissible and the endowed cash can be utilized for the investment and income-generation in various sectors for socio-economic development. Instances can be found in the context of many Muslim individuals, non-government and government organizations who initiated to establish the institution of waqf for generating incomes, eradicating the poverty, creating new job market and helping poor and needy people. Given the context, there is a need to examine the legitimacy of cash waqf, its role and application. The paper will survey the meaning, necessity, and brief history of cash waqf and examine the roles of cash waqf in providing various services to the deferent sectors and finally, present the Islamic perspective on the issue. The paper also briefly reviews the responses of Muslim scholars with a textual analysis and inductive approach to analyze the prospects of formulating an Islamic stance on cash waqf in current context. It is also hoped that the ideas raised will ultimately contribute to understanding and clarifying the Islamic stance on the issue for both Muslim and non-Muslim communities in contemporary society.